2021
DOI: 10.3390/ijerph182312283
|View full text |Cite
|
Sign up to set email alerts
|

Association of Occupational Distress and Low Sleep Quality with Syncope, Presyncope, and Falls in Workers

Abstract: Syncope and presyncope episodes that occur during work could affect one’s safety and impair occupational performance. Few data are available regarding the prevalence of these events among workers. The possible role of sleep quality, mental stress, and metabolic disorders in promoting syncope, presyncope, and falls in workers is unknown. In the present study, 741 workers (male 35.4%; mean age 47 ± 11 years), employed at different companies, underwent clinical evaluation and blood tests, and completed questionna… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…In our cohort, personality traits, apart from neuroticism, were not associated with the recurrence of syncope or the type of underlying origin, which may also have been due to the small number of patients included. These syncopes might be possibly addressed by psychological interventions, so that a thorough identification of possible stressors and risk factors is mandatory in the assessment of syncopes, in line with the results by Magnavita et al described in the introduction [ 14 ].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In our cohort, personality traits, apart from neuroticism, were not associated with the recurrence of syncope or the type of underlying origin, which may also have been due to the small number of patients included. These syncopes might be possibly addressed by psychological interventions, so that a thorough identification of possible stressors and risk factors is mandatory in the assessment of syncopes, in line with the results by Magnavita et al described in the introduction [ 14 ].…”
Section: Discussionsupporting
confidence: 53%
“…A similar observation was reported by Magnavita et al, who showed that the risk for syncope was higher in patients with occupational distress, a low sleep quality and poor mental health. The authors reasoned that health promotion interventions could reduce syncopes via reducing sleep quality and reducing (work-associated) stressors [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of each survey were reported to the companies, the corporate prevention service, and the workers’ safety representatives in order to contribute to the growth of the work culture. Besides offering workers advice and providing companies with useful indications, WHPEMS activities have enabled researchers to produce some scientific publications [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. Furthermore, by annually reiterating surveys on the same cohorts of workers, it has been possible to carry out longitudinal studies to clarify the causal link between exposure to risk and damage to health [ 64 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…This unprecedented situation placed healthcare workers (HCWs) at high risk to experience affective responses [2,3]. In fact, previous findings indicate that HCWs commonly experienced depression, anxiety, burnout (i.e., response to chronic stress at workplace, including emotional exhaustion, depersonalization and capacities reduction) [4] and secondary traumatic stress symptoms (i.e., STS; compassion fatigue and stress resulting from helping others) [5], during the COVID-19 outbreak [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%